Detecting changes in the Arctic Ecosystem – Long-Term Benthos Monitoring network for detecting changes in the Arctic benthic ecosystem (LTM-Benthos) 2017-2020 - Jørgensen, Lis Lindal; Blicher, Martin; Bluhm, Bodil; Christiansen, Jørgen Schou; Fredriksen, Rosalyn; Hammeken, Nanette; Logerwell, Libby; Olafsdottir, Steinunn Hilma; Roy, Virginie; Strelkova, Natalia A.; Sørensen, Jan; Thangstad, Trude Hauge (Havforskningsinstituttet, 2018)
Source at https://www.imr.no/filarkiv/detecting_changes_in_the_arctic_ecosystem.pdf/nn-no . Introduction : Main purpose of this group is data exploration. For example, megafaunal community characterization, modeling of variables that influence these communities (environment, stressors, etc.). Scaling of data matters: Depending on the objectives, required resolution of the data and analyses will vary, e.g. for managing trawl closures, fine-scale analyses are required; for understanding ecosystem change, broad-scale analyses are required. Next steps include understanding potential outcomes and the limitations of the data analyses: identifying what management questions we can answer with existing baseline data, and what agencies/groups etc. would be users of our results. Propose analyses and management uses of continued future monitoring, to emphasize value of long-term monitoring.